Former Yugoslav Republic of Macedonia : Selected Issues for the 2009 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2010)
This Selected Issues paper assesses the desired level of foreign exchange reserves in the Former Yugoslav Republic of Macedonia, given its commitment to maintain the exchange rate peg. A variety of methods including popular rules of thumb, comparisons with other emerging countries, and model-based estimates suggest a target range of Euro 1.5-2 billion for reserves. The paper also looks at reserve levels that would be implied by popular rules of thumb and at benchmarks suggested by other emerging market countries.